S-30-5: DIETARY PATTERNS AND CARDIOVASCULAR AND KIDNEY PHENOTYPES IN AN URUGUAYAN POPULATION COHORT. (January 2023) - Moliterno, Paula; Donangelo, Carmen Marino; Borgarello, Luciana; Pécora, Matías; Olascoaga, Alicia; Noboa, Oscar; Boggia, José
Abstract : The impact of habitual diet on chronic diseases has not been extensively characterized in South America, were cardiovascular risk factors are highly prevalent. Although aging plays an important and unavoidable role in the development of chronic diseases, sustained exposure to unhealthy diets fastens physiological and morphological changes leading to early vascular aging and premature advancement of disease. We aimed to identify major dietary patterns (DP) in an adult cohort in Uruguay (Genotype Phenotype and Environment of Hypertension Study, GEFA HT UY) and to assess associations with metabolic, anthropometric characteristics, and cardiovascular and kidney phenotypes. In a cross-sectional study (n = 294), dietary information was collected through an interview using an adapted food frequency questionnaire and DP were derived by the principal component analysis. Blood and urine parameters, anthropometrics, blood pressure, pulse wave velocity, and glomerular filtration rate were measured. Multivariable adjusted linear models and adjusted binary logistic regression were used. Three DP were identified (Meat, Prudent, Cereal and Mate) explaining 22.6% of total variance in food intake. The traditional Meat DP, characterized by red and barbecued meat, processed meat, bread, and soft drinks, was associated with worse blood lipid profile. Prudent DP, characterized by vegetables, fish, and nuts, and lower loads for bread and crackers, was associated with reduced risk of vitamin D deficiency. Cereal and Mate DP, was characterized by higher loads of cereals, bread, and crackers, and mate infusion, with higher odds of excessive body weight. No direct associations of dietary patterns with hypertension, arterial stiffness, chronic kidney disease, and nephrolithiasis were found in the studied population, nor by age categories or sex.